SAT0003 The IL-20 Receptor Axis in Early Rheumatoid Arthritis: Novel Inflammation-Independent Links Between Rheumatoid Arthritis-Associated Autoantibodies and Radiographic Progression. (9th June 2015) - Kragstrup, T.W.; Greisen, S.R.; Nielsen, M.A.; Rhodes, C.; Stengaard-Pedersen, K.; Hetland, M.L.; Hørslev-Petersen, K.; Junker, P.; Østergaard, M.; Hvid, M.; Vorup-Jensen, T.; Robinson, W.; et al.
Abstract : Background: Rheumatoid arthritis (RA) is characterized by high occurrence of rheumatoid factor (RF), anti-citrullinated protein antibodies (ACPAs) and bone erosions. Successful treatment with biologic drugs such as anti-tumor necrosis factor alpha compromises the normal immune response increasing the risk of infections. The interleukin 20 receptor (IL-20R) axis comprising IL-19, IL-20, and IL-24 ("the IL-20R cytokines") and their shared receptors IL-20R2/IL-20R1 and IL-20R2/IL-22R activates tissue homeostasis processes but not the immune system (Figure 1 ). Objectives: The objective of this study was to determine the role of the IL-20R axis in early RA (eRA) with focus on associations of the three cytokines with clinical disease activity and prognosis. Methods: The IL-20R cytokines were measured in plasma samples from treatment naïve early RA patients during 24 months of treatment with methotrexate, adalimumab/placebo and intra-articular glucocorticoid injections (the OPERA trial) (n=152) 1 . The IL-20R1 and IL-22R expression was studied in paired peripheral blood and synovial fluid cells from a different cohort of RA patients (n=15) with at least one swollen joint (for obtaining synovial fluid) by flow cytometry and confocal microscopy. Heat aggregated human gamma globulins (HAGGs) and immune complexes containing citrullinated fibrinogen (cFb-ICs) were used to stimulate myeloid cells. Osteoclasts (OCs) derived from synovial fluid cells were used to assess the effect of the IL-20R cytokines. Results: The plasma concentrations of IL-20 and IL-24 (but not IL-19) were increased in eRA patients compared with HCs (both P< 0.002) and decreased after 6 months of treatment (both P <0.0001). The expression of IL-22R (but not IL-20R1) was increased on monocytes from RA synovial fluid compared with RA and HC peripheral blood. The plasma concentrations of IL-20 and IL-24 were increased in RF and ACPA positive compared with negative eRA patients (all P <0.0001). HAGGs and cFb-ICs stimulated the production of the IL-20R cytokines by myeloid cells. Increased baseline plasma concentrations of IL-20 and IL-24 associated with radiographic progression (evaluated by the total Sharp-van der Heijde score) after 12 months (Spearman's rho=0.27 and 0.23, both P <0.005) and 24 months (Spearman's rho=0.19 and 0.26, both P <0.05) in the eRA patients. No associations were observed between concentrations of the IL-20R cytokines and disease activity. The IL-22R was expressed by RANK + OC precursors and in multinucleated TRAP + OCs and these cells were activated by IL-20 and IL-24. Conclusions: Inflammation-independent associations of the IL-20R axis with RA-associated autoantibodies and radiographic progression in eRA were detected. Our data support that dual inhibition of IL-20 and IL-24 or attenuation of the shared IL-22R subunit could attenuate radiographic progression without compromising the normal immune response especially in seropositive RA. References: Hørslev-Petersen et al. Ann Rheum Dis. 2013. Disclosure of Interest: None declared